AN ANALYSIS OF STUDENT’S RECOUNT TEXT IN SYSTEMIC FUNCTIONAL LINGUISTIC PERSPECTIVES - Ni Kadek Heny Sayukti; Eri Kurniawan (RETORIKA: Jurnal Ilmu Bahasa, 2018)
As a demand of English learning, eighth grade students need to be able to write a recount text about their personal experiences. For this reason, this study employs a qualitative case study research design to analyse students’ writing of recount text. The data were obtained by collecting students’ writing in two different classes of eight grade junior high school in Bandung, Indonesia during the even semester of academic year 2016/2017. The self-composed recount texts were selected based on different proficiency levels as suggested by the English teacher of the school. For the framework of the text analysis, this study draws on Systemic Functional Linguistic theory, and recount text. Meanwhile, content analysis was employed to explore the analysis of the writing. The results presented that majority of problems on the students’ writings consist of social function and language feature. In terms of language features, there were still several errors in spelling, punctuation and capitalization. In term of Interpersonal metafunction, errors usually occurred in the Finite as there was an overlap of past tense and present tense. As a result, it was found that most of the clauses were written in material process and it still lack of reference in the theme-rheme structure.